2022
DOI: 10.1038/s41598-022-26257-0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously implemented spatial coherence in vertical-cavity surface-emitting laser dot array

Abstract: We report a self-induced spatially-coherent dot array consisting of fourteen units of vertical-cavity surface-emitting modes that exhibit spatially uniform spectra. A 47.5 µm total beam width and 0.5° narrow emission are achieved using an oblong cavity enclosed with a flat top mirror, cylindrically curved bottom mirror, and side facet. Notably, terminating the side of the cavity with a perpendicular facet enhances the horizontal propagation, which couples with the vertical resonance in each dot, similar to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The curved mirror provided lateral optical confinement to eliminate the diffraction loss, thereby improving the laser characteristics. After the report of operation under pulsed current injection in 2018 [9], blue VCSELs with similar structures, efficient current confinement by ion implantation [10], sub-milliampere operation [11], stabilized lateral modes [12], high efficiency operation up to 13.5% [13] (see Figure 1a), long life reaching 2000 h [14], generation of spatially coherent dot array of VCSEL modes [15], and narrow emission angle of 3.9° for circular aperture [16] and 0.5 degree for oblong aperture [17] have been reported. Recently, we reported CW-operation green VCSELs [18] with milliwatt class outputs and high-efficiency operation [19] (see Figure 1b).…”
Section: Vcsel With Curved Mirror and Long Cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…The curved mirror provided lateral optical confinement to eliminate the diffraction loss, thereby improving the laser characteristics. After the report of operation under pulsed current injection in 2018 [9], blue VCSELs with similar structures, efficient current confinement by ion implantation [10], sub-milliampere operation [11], stabilized lateral modes [12], high efficiency operation up to 13.5% [13] (see Figure 1a), long life reaching 2000 h [14], generation of spatially coherent dot array of VCSEL modes [15], and narrow emission angle of 3.9° for circular aperture [16] and 0.5 degree for oblong aperture [17] have been reported. Recently, we reported CW-operation green VCSELs [18] with milliwatt class outputs and high-efficiency operation [19] (see Figure 1b).…”
Section: Vcsel With Curved Mirror and Long Cavitymentioning
confidence: 99%
“…Figure 1. I-V/L and I-WPE curves of (a) blue [13] and (b) green VCSELs [17] with curved mirror. Insets are emission spectra obtained above threshold currents.…”
Section: Vcsel With Curved Mirror and Long Cavitymentioning
confidence: 99%
“…In 2003, Park et al reported the operation of a GaN-based VCSEL with monolithic curved mirrors, optically pumped [25]. Over the past few years, various VCSEL structures with curved mirrors have been demonstrated [8,9,[26][27][28][29][30][31][32][33]. Recently, it was demonstrated that upper DBR mirrors can be successfully replaced by high-index contrast gratings (HCG) and monolithic high-refractive-index contrast gratings (MHCG).…”
Section: Introductionmentioning
confidence: 99%